Cisco Cookbook - Brown, Ian J. (O'Reilly, 2011)
Never has something cried out for a cookbook quite as much as Cisco's Internetwork Operating System (IOS). IOS is powerful and flexible, but also confusing and daunting. Most tasks can be accomplished in several different ways. And you don't want to spend precious time figuring out which way is best when you're trying to solve a problem quickly.